Nursing students' perceptions and attitudes towards dementia care in Namibia - Nestor Tomas; Andrias M. Mangundu (AOSIS, 2024)
Background: Dementia is a significant public health concern and a leading cause of disability and dependency among elderly individuals globally. However, there is currently limited research examining the perceptions and attitudes of healthcare providers, including nursing students, in Namibia. Aim: This study aimed to examine nursing students' perceptions and attitudes of caring for patients with dementia. Setting: The study was conducted at two university campuses in Namibia. Methods: A quantitative correlational design was employed to conveniently recruit 196 third- and fourth-year nursing students between April and August 2023, utilising the Geriatric In-Hospital Nursing Care Questionnaire (GerINCQ) online survey. Data were analysed using SPSSv28 for descriptive and inferential statistics. Results: The perception score ranged from 2.26 to 2.43, indicating negative attitudes and perceptions towards dementia care. The highest mean perception of 2.43 (95% CI = 2.3-2.55) was on reacting to challenging behaviour and the lowest was on professional responsibility 2.26 (95% CI = 2.12-2.4). Correlations were observed between age and performed interventions (r = 0.66; p = 0.01) and gender and dementia-sensitive care (r = 0.52; p = 0.01). Conclusion: The study revealed unfavourable attitudes and perceptions towards dementia care among nursing students, contrary to the optimistic anticipation. The results highlight the urgent need to develop and integrate dementia care strategies and practices into nursing education curricula. Contribution: This study provides valuable data for informing quality assurance initiatives aimed at improving nursing training in dementia care.